Detection of rotavirus in paediatric oncology patients with diarrhoea: the impact of rotavirus vaccine. Issue 2 (June 2018) - Akhtar, T.; Cargill, J.; Gerrard, C.; Shaw, F.; Cunliffe, N.A.; Cooke, R.P.D.; Pizer, B.
Summary: Seven years' data were reviewed to examine stool-testing for rotavirus in patents treated in a regional paediatric oncology unit before and after the introduction of UK-wide rotavirus immunization in July 2013. The prevalence of rotavirus positivity has diminished since the introduction of rotavirus immunization, with 21 of 416 positive samples between 2010 and 2012, but only one positive test out of 122 samples in 2015 and 2016. Based on these results, there seems to be little use for routine rotavirus-testing in children and young people with cancer presenting with diarrhoea.